Hip disarticulation - case series analysis and literature review - Moura, DL (2017)
OBJECTIVE: To present a retrospective study of 16 patients submitted to hip disarticulation. METHODS: During the period of 16 years, 16 patients who underwent hip disarticulation were identified. All of them were studied based on clinical records regarding the gender, age at surgery, disarticulation cause, postoperative complications, mortality rates and functional status after hip disarticulation. RESULTS: Hip disarticulation was performed electively in most cases and urgently in only three cases. The indications had the following origins: infection (n = 6), tumor (n = 6), trauma (n = 3), and ischemia (n = 2). The mean post-surgery survival was 200.5 days. The survival rates were 6875% after six months, 5625% after one year, and 50% after three years. The mortality rates were higher in disarticulations with traumatic (66.7%) and tumoral (60%) causes. Regarding the eight patients who survived, half of them ambulate with crutches and without prosthesis, 25% walk with limb prosthesis, and 25% are bedridden. Complications and mortality were higher in the cases of urgent surgery, and in those with traumatic and tumoral causes. CONCLUSION: Hip disarticulation is a major ablative surgery with obvious implications for limb functionality, as well as high rates of complications and mortality. However, when performed at the correct time and with proper indication, this procedure can be life-saving and can ensure the return to the home environment with a certain degree of quality of life.